The “eye sign” due to hemispatial neglect. A case report - Fábio Henrique de Gobbi Porto (Dementia & Neuropsychologia, 2009)
Conjugate eye deviation is characterized by a sustained shift in horizontal gaze, usually toward the affected brain hemisphere. When detected on neuroimaging, it is called the “eye sign”. It is classically associated with lesions involving the frontal eye fields, ipsilateral to the side of the deviation. Neglect may be conceptualized as a spatially addressed bias of the sensory events in explicit behaviors and in the absence of perceptual and motor deficits. Hemispatial neglect is a common disabling condition that occurs following acute unilateral brain damage, usually to the right side. We report a case of a patient presenting with the “eye sign” on tomography, following an acute subinsular stroke, in the absence of conjugated eyes deviation. Our hypothesis was that the sign may have been due to hemispatial neglect in this patient. The aim of this article was to discuss the mechanisms involved in the attention network and its neuroanatomic correlates.